(untitled) (International Journal of Architecture and Urbanism, 2024)
In the case of an emergency, effective evacuation is crucial to minimize losses. This paper focuses on analyzing and designing efficient evacuation routes for Rusunawa Putri UII in Yogyakarta, a dormitory building. It emphasizes ensuring safety during fires or earthquakes, particularly in densely populated structures. The research aims to enhance evacuation route efficiency through a thorough examination of layout, accessibility, and capacity. It utilizes the Pathfinder methodology, a robust analytical framework for simulating and analyzing pedestrian movement in evacuation scenarios. The study evaluates existing routes using field observations, simulations, and statistical analysis to identify areas that need improvement. The findings will guide decision-makers in optimizing evacuation plans and strengthening safety measures in similar densely populated residential buildings.